Nanowire Electronics - Shen, Guozhen; Chueh, Yu-Lun.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book gives a comprehensive overview of recent advances in developing nanowires for building various kinds of electronic devices. Specifically the applications of nanowires in detectors, sensors, circuits, energy storage and conversion, etc., are reviewed in detail by the experts in this field. Growth methods of different kinds of nanowires are also covered when discussing the electronic applications. Through discussing these cutting edge researches, the future directions of nanowire electronics are identified.
Carbon Nanotubes for Flexible and Transparent Electronics -- Metal Oxide Nanowires for Flexible Electronics -- One-dimensional II-VI Group Semiconductor Nanostructures for Nano-electronics -- Developing Nanowires for Transparent and Flexible Electrodes -- Nanowires for Microelectronics -- Nanowires for Energy -- Wafer-scale Integrated Circuits Based on Aligned Carbon Nanotubes -- Field Emitters with Carbon Nanotubes.
Keywords: Nanotechnology; Energy storage; Electronic circuits; Optical materials; Semiconductors; Nanotechnology; Mechanical and Thermal Energy Storage; Electronic Circuits and Systems; Optical Materials; Semiconductors